The Study on Relationship between Social Capital and Site Potential: Case study of Thakhlong Municipality, Pathumthani - Iamtrakul, Pawinee; Klaylee, Jirawan (Journal of Architectural/Planning Research and Studies (JARS), 2018)
The importance of social capital has been changed according to the movement of urban development in term of socio-economic and environmental aspects. Physical transformation of urban development directly affected people living, particularly travelling pattern and social interactions. Furthermore, unplanned and insufficient development of urban infrastructure has also caused considerable impacts on daily activities. This study selected Tha-Khlong municipality, Pathumthani province as a case study for an analysis of the relationship between the social capital factors and the site potential factors. The finding of non-physical aspects would indicate social challenges that arise in the study area. Moreover, spatial analysis through the Geographic Information System (GIS) would show spatial allocations of infrastructure services and level of social dimensions. Next statistical technique of cluster analysis could address eight groups of clustering that present of socio-economic profiles of lifestyles in the study area. Their different behaviors could explain current challenges and opportunities. Finally, land use planning guidelined enhancing social interaction and social capital improvement would be mentioned.